Coupled Ocean-Atmosphere Mode in the Tropical Indian Ocean during 2011 - Iskandar, Iskhaq; Mardiansyah, Wijaya; Setiabudidaya, Dedi (UI Scholars Hub, 2014)
Coupled ocean-atmosphere mode in the tropical Indian Ocean, so-called the Indian Ocean Dipole (IOD), occurred